2019
DOI: 10.3390/ijerph16010108
|View full text |Cite
|
Sign up to set email alerts
|

Engagement, Passion and Meaning of Work as Modulating Variables in Nursing: A Theoretical Analysis

Abstract: Nurses are continuously exposed to stressors and psychological and physical risks that can negatively influence their daily work. These adverse psychosocial circumstances, accompanied by the poor self-perception of health, well-being, and quality of life, may trigger burnout. The positive psychology approach pursues a growth of passion at work, increased job satisfaction, and occupational health, both mental and physical, for the optimal performance of the nursing role. In this way, a theoretical analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 39 publications
0
64
0
3
Order By: Relevance
“…Working in a hospital can involve both physical risks and psychological strain for nurses (Gomez‐Salgado et al, 2019). Dealing with the hardships in this profession may require “more than monetary and/or job security rewards” (Malloy et al, 2015, p. 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Working in a hospital can involve both physical risks and psychological strain for nurses (Gomez‐Salgado et al, 2019). Dealing with the hardships in this profession may require “more than monetary and/or job security rewards” (Malloy et al, 2015, p. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Pavlish and Hunt (2012) reported that nurses who take on a managerial role experience a greater sense of work meaning and satisfaction by “improving the quality of care by nurturing opportunities” (p. 113). When work becomes excessively task‐centred and ignores relationships, meaningfulness in work may decrease substantially among nurses.In general, finding work meaningful does contribute to both task and contextual performances (Gómez‐Salgado et al, 2019; Tong, 2018), job satisfaction and mental and physical occupational health (Gómez‐Salgado et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement is positively influenced by the diversity and complexity of work activities, organizational support, autonomy, exchange of leaders, problem-solving ability, exchange of team members, and friendship in workplace positively influence levels of engagement. Negative influences can include working conditions, physical demands, and stress (Dasgupta, 2016;Gómez-Salgado, Navarro-Abal, López-López, Romero-Martín, & Climent-Rodríguez, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Intent to resign and job burnout are related to professional identity [11,12] . However, there has been little research on the professional identity of GPs in China; it has been suggested that this is dynamic and depends on social context.…”
Section: Introductionmentioning
confidence: 99%